WILLINGNESS TO PAY FOR PUBLIC ECOTOURISM SERVICES IN MALAYSIA - Ding, Hun Shuang; Alias, Anuar (Journal of Technology Management and Business, 2014)
The main focus of this study is to determine the attributes of willingness-to-pay (WTP) of the general public towards the entrance fee for using services in the Public Ecotourism Organization. Contingent Valuation Method is used to estimate the value of non-market good by adopting WTP approach. WTP is the maximum amount consumers are prepared to pay for a good or service and to enjoy recreational facilities. It measures whether an individual is willing to forego their income in order to obtain more goods and better services, and WTP is typically used for non-market goods. This study adopted questionnaires survey to examine the perception on the willingness to pay by visitors for the fees charged by the authorities for the services they provided. 100 local and international respondents among visitors involved in the study. The findings showed that National Park can give a new experience to visitors with beautiful natural landscape. However, the respondents perceived that road linkages of National Park are not proper and fee charged for boat services a bit too high. While, National Zoo is visited mostly to spend time and holiday with family due to attractive wildlife shows available daily. The authority however, needs to improve on hygienic aspect and perhaps to lower down the entrance fees. The attractiveness and shortcoming of the National Park and National Zoo are identified in order to suggest for improvements of services to public. As the economic growth, people will demand for better services and facilities or else willingness to pay will be affected. Thus, it is important for the government organizations to upgrade their services and facilities over time to fulfill the needs of the people.